Between Poverty and Ngalap Berkah (Seeking for Blessings) Myth: Contradiction of Welfare Perception Among Tobbacco Farmers in di Temanggung - Abdila; Lestariningsih, Wahyu; Savana, Devina; Tunnisa, Ana Fitro; Suyatna, Hempri (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2024)
Tobacco farmers in Temanggung Regency, the largest and best tobacco producing region in Central Java, still have low incomes. However, local farmers still cultivating tobacco and believed that tobacco is a "tanaman wali" that brings blessings to farmers, so ritual practices similar to ngalap berkah are carried out to gain good luck when harvesting tobacco. This research aims to dissect the cultural factors that influence the economic behavior of Temanggung tobacco farmers and their perceptions regarding welfare. This research method is ethnography with the help of a historical perspective. Data was obtained from field observations and in-depth interviews, welfare data archives at social services, BPS data archives, and scientific literature. Data analysis was carried out using a process of verification, reduction, interpretation and triangulation. The research results show that historical factors in the form of farmers' debt bondage with Chinese middlemen, which are mystified in tobacco myths, are the reason why farmers find it difficult to switch to other commodities. Belief in these myths also creates a perception of prosperity that is inverted from the reality of the tobacco economy, but fosters other sources of welfare that are subjective with three dimensions including harmony, social relations and the environment. Keywords. tobacco farmers, subjective-well being, contradiction, ngalap berkah, Temanggung.